Kwestie konfesyjne w kontaktach polsko-angielskich (i brytyjskich) w XVI i XVII wieku - Grzebyk, Tomasz (Uniwersytet Rzeszowski, 2023)
Niniejsza rozprawa doktorska skupia się na analizie kon-taktów pomiędzy Rzecząpospolitą a Wyspami Brytyj-skimi w XVI i XVII wieku, z naciskiem na kwestie konfe-syjne oraz pokazuje w jaki sposób sprawy religijne wpływały na stosunki między tymi krajami na różnych płaszczyznach: polityki międzynarodowej, reformacji i reformy katolickiej, aż po kontakty prywatne. W pierwszym rozdziale autor omawia polityczny i dyplomatyczny wymiar tych kontaktów, w tym próby zawiązania antymuzułmańskiej koalicji oraz rolę wy-znawanej konfesji w kontekście mariaży dynastycznych. Drugi rozdział skupia się na roli polskich protestantów w rozwoju reformacji w Anglii, analizując działalność Jana Łaskiego i ideologię Braci polskich, a także związki polskich i litewskich wyznawców Kalwina z Anglią i Szkocją. Trzeci rozdział dotyczy kwestii związanych z reformą katolicką i skupia się na roli kardynała Hozjusza w kształtowaniu postaw angielskich katolików, Rzeczy- pospolitej jako miejscu azylu dla brytyjskich wygnańców religijnych oraz podkreśla wpływ angielskiej literatury martyrologicznej na kształtowanie się antyprotestanc-kich postaw mieszkańców Rzeczypospolitej w XVII w.. Czwarty rozdział analizuje rolę podróżników, kupców i żołnierzy w kontaktach polsko-angielskich, zwracając uwagę na transfer informacji religijnych oraz na to, jak oba kraje były postrzegane przez podróżników z oby-dwu krajów.

This doctoral dissertation focuses on the analysis of contacts between the Polish-Lithuanian Common-wealth and the British Isles in the 16th and 17th centu-ries, emphasizing confessional issues and demonstrat-ing how religious matters influenced the relations be-tween these countries at various fields. In the first chapter, the author discusses the political and diplomatic dimension of these contacts, including attempts to establish an anti-Muslim coalition and the role of professed confession in the context of dynastic marriages. The second chapter focuses on the role of Polish Protestants in the development of the Reformation in England, as well as the connections of Polish and Lithu-anian followers of Calvin with England and Scotland. The third chapter deals with issues related to the Catholic reform and focuses on the role of Cardinal Ho-sius in shaping the attitudes of English Catholics, the Commonwealth as a place of asylum for British religious exiles, and highlights the influence of English martyro-logical literature on shaping anti-Protestant attitudes among the inhabitants of the Commonwealth in the 17th century. The fourth chapter analyzes the role of travelers, mer-chants, and soldiers in Polish-English contacts, paying attention to the transfer of religious information and how both countries were perceived by travelers from both nations.
Confessional issues in Polish-English (and British) rela-tions in the 16th and 17th centuries
Promotor: ks. prof. dr hab. Stanisław Nabywaniec - 202 s.
Keywords: reformacja; reforma katolicka; Polska; Anglia; XVI-XVII wiek; reformation; catholic reformation; Poland; England 16th-17th centuries